Applying aspects to a real-time embedded operating system - Afonso, Francisco (2007)
The application of aspect-oriented programming (AOP) to the embedded operating system domain is still a very controversial topic, as this area demands high performance and small memory footprint. However, recent studies quantifying aspects overheads in AspectC++ show that the resource cost is very low. Therefore, operating system development may benefit with the modularization of crosscutting concerns and system specialization offered by AOP. This paper addresses our experience in applying aspects to synchronization (mutual exclusion) and logging in a real-time embedded operating system (BOSS). Furthermore, we present our ideas for future investigation in aspect-oriented implementations for fault tolerance, middleware customization and platform variability.